‘Mind’ and ‘mental’: extended, pluralistic, eliminated - Gough, J (Springer, 2024)
The terms ‘mind’ and ‘mental’ are used to refer to different phenomena across and within at least philosophy, psychology, psychiatry, and cognitive science. My main aim in this paper is to argue that the terms ‘mind’ and ‘mental’ are in this way ‘pluralistic’, and to explore the different options for responding to this situation. I advocate for a form of pluralistic eliminativism about the terms ‘mind’ and ‘mental’, ‘mind concept eliminativism,’ because I believe that current use of the terms results in both public and scientific confusions that hamper progress on important issues and increase stigma around certain vulnerable groups.